Seismogenesis and Earthquake Forecasting: The Frank Evison Volume II 2010
DOI: 10.1007/978-3-0346-0500-7_2
|View full text |Cite
|
Sign up to set email alerts
|

First Results of the Regional Earthquake Likelihood Models Experiment

Abstract: Abstract-The ability to successfully predict the future behavior of a system is a strong indication that the system is well understood. Certainly many details of the earthquake system remain obscure, but several hypotheses related to earthquake occurrence and seismic hazard have been proffered, and predicting earthquake behavior is a worthy goal and demanded by society. Along these lines, one of the primary objectives of the Regional Earthquake Likelihood Models (RELM) working group was to formalize earthquake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 34 publications
5
56
0
Order By: Relevance
“…These tests were applied to the raw submitted data. This approach was applied to the first 2.5 years of RELM results by Schorlemmer et al [13]. Zechar et al [21] recognized a problem with the original proposed likelihood tests and proposed a modification.…”
Section: Evaluation Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These tests were applied to the raw submitted data. This approach was applied to the first 2.5 years of RELM results by Schorlemmer et al [13]. Zechar et al [21] recognized a problem with the original proposed likelihood tests and proposed a modification.…”
Section: Evaluation Of Resultsmentioning
confidence: 99%
“…The submitted forecasts have been discussed in some detail [13]. The nineteen forecasts submitted by eight groups are available on the RELM website (http://relm.cseptesting .org/).…”
Section: Submitted Forecastsmentioning
confidence: 99%
“…A well‐known example of such a statistical model is the Epidemic‐Type Aftershock Sequence (ETAS) model, in which earthquake occurrence is treated as a point process and space, time, and magnitude kernels are typically assumed to be independent [ Ogata , ]. These types of statistical models have had good success in retrospective and prospective forecasting of moderate‐magnitude earthquakes ( M < 5) [ Schorlemmer et al ., ] but have been criticized for ignoring the physical processes of stress transfer and relaxation. Previous attempts to combine ETAS and finite‐fault‐based models have found that some elements of elastic rebound and stress relaxation must be included in order to prevent self‐exciting aftershock sequences from “blowing up” [ Field , , ].…”
Section: Introductionmentioning
confidence: 99%
“…The space and time variations of the seismic parameters in a given region are often considered as indicators of changes in the seismicity regime, eventually announcing the occurrence of a large earthquake (e.g. Schorlemmer et al 2010). Among the seismic parameters whose variations are studied, the most popular are certainly the amplitude, M. Bengoubou-Valérius Bureau de Recherche Géologiques et Minières Guadeloupe, Morne Houëlmont, Route de l'Observatoire, 97113 Gourbeyre, France e-mail: m.bengoubou-valerius@brgm.fr D. Gibert (&) Institut de Physique du Globe de Paris (CNRS UMR 7154), Sorbonne Paris Cité, 1 rue Jussieu, 75238 Paris cedex, France e-mail: gibert@ipgp.fr A, and the exponent, b, of the Gutenberg-Richter (GR) power-law distribution of earthquake magnitudes (Gutenberg and Richter 1944;Main 2000),…”
Section: Introductionmentioning
confidence: 99%